Cultural Animal Reader for Baumeister/Bushman's Social Psychology and Human Nature - Feinberg, Joshua (Thomson, 2008)
The CULTURAL ANIMAL READER contains full-text articles, referenced within the main text, that relate to the book's overarching themes. Critical thinking questions for each chapter are included